Analyzing the Complementary Relationship Between the Auditor’s Commitment to Applying Isa 580 and Obtaining Audit Evidence, and Its Impact on Detecting Material Misstatements and Enhancing the Reliability of Financial reports.analyzing the Complementary R - Sohad Sabih Alsaffar; Istiqlal Jumaah Wajar; Noor Sabah Hussein (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Financial reports serve as a primary source for economic decision-making, making their reliability and credibility essential, while external auditing provides assurance through sufficient and appropriate audit evidence. Specific Background Written management representations, as regulated by ISA 580, constitute a supporting component of audit evidence used by auditors to form professional opinions regarding financial statements. Knowledge Gap Despite their recognized role, limitations remain regarding the sufficiency of written representations as standalone evidence and their capacity to fully support the detection of material misstatements. Aims This study examines the relationship between auditors’ obligation to apply ISA 580 and the process of collecting audit evidence, as well as its association with identifying material misstatements in financial reports. Results The findings indicate that written management statements provide general assurances but lack sufficient supporting evidence and disclosure, functioning primarily as complementary audit tools. Weaknesses were also identified in accounting measurement and internal control systems, increasing the likelihood of misstatements. Novelty The study highlights the conditional role of written representations as supportive rather than primary audit evidence within the audit process. Implications These findings suggest the necessity for auditors to integrate written representations with other audit procedures to strengthen the reliability of financial reporting and improve audit judgment. Highlights:• Written representations provide limited evidential support without corroborating procedures• Internal control and accounting weaknesses increase misstatement risk• Audit evidence requires integration beyond formal management declarations Keywords: ISA 580, Audit Evidence, Written Management Representations, Material Misstatements, Financial Report Reliability